Nutritional epigenomics - Ferguson, Bradley S. (Translational epigenetics series, 2019)
"Nutritional Epigenomics offers a comprehensive overview of nutritional epigenomics as a mode of study, along with nutrition's role in the epigenomic regulation of disease, health and developmental processes. Here, an expert team of international contributors introduces readers to nutritional epigenomic regulators of gene expression, our diet's role in epigenomic regulation of disease and disease inheritance, caloric restriction and exercise as they relate to recent epigenomic findings, and the influence of nutritional epigenomics over circadian rhythms, aging and longevity, and fetal health and development, among other processes. Disease specific chapters address metabolic disease (obesity and diabetes), cancer, and neurodegeneration, among other disorders."--Provided by publisher